2018
DOI: 10.1242/jcs.208926
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN promotes formation of signaling-capable clathrin-coated pits

Abstract: Defective endocytosis and vesicular trafficking of signaling receptors has recently emerged as a multifaceted hallmark of malignant cells. Clathrin-coated pits (CCPs) display highly heterogeneous dynamics on the plasma membrane where they can take from 20 s to over 1 min to form cytosolic coated vesicles. Despite the large number of cargo molecules that traffic through CCPs, it is not well understood whether signaling receptors activated in cancer, such as epidermal growth factor receptor (EGFR), are regulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…In this contention, we note that clustering of signaling receptors into CCPs has been proposed as a mechanism to regulate signaling magnitude at the PM (reviewed by Barbieri et al., 2016 ). In particular, EGFR recruitment into CCPs was proposed to spatially constrain otherwise short-lived EGFR dimers and to amplify receptor activation ( Rosselli-Murai et al., 2018 , Ibach et al., 2015 ). Thus, AP2 might be instrumental in assembling PM-based signaling platforms.…”
Section: Discussionmentioning
confidence: 99%
“…In this contention, we note that clustering of signaling receptors into CCPs has been proposed as a mechanism to regulate signaling magnitude at the PM (reviewed by Barbieri et al., 2016 ). In particular, EGFR recruitment into CCPs was proposed to spatially constrain otherwise short-lived EGFR dimers and to amplify receptor activation ( Rosselli-Murai et al., 2018 , Ibach et al., 2015 ). Thus, AP2 might be instrumental in assembling PM-based signaling platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, both dynasore and Dyngo-4a have been shown to have numerous off-target effects unrelated to CME ( Park et al, 2013 ; Persaud et al, 2018 ). Similarly, pitstop is cytotoxic at concentrations only approximately twofold higher than its reported inhibitory effects on CME ( Rosselli-Murai et al, 2018 ) and has been shown to perturb both spindle pole assembly and nucleocytoplasmic permeability ( Smith et al, 2013 ; Liashkovich et al, 2015 ), although both of these effects have been ascribed to so-called moonlighting functions of clathrin ( Brodsky et al, 2014 ). In contrast, our demonstration that Wbox2 peptide binds AP2 and SNX9 and inhibits AP2–TD interactions at concentrations similar to its inhibitory effects in cells, and that these properties are lost upon mutation of key residues shown to be important for Wbox binding activity, provide a strong basis for the on-target effects of this peptide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pitstop also inhibits clathrin-independent endocytosis (CIE) of multiple cargoes, even in clathrin-depleted cells ( Dutta et al, 2012 ), and inhibits Tfn uptake via CME even in cells expressing Cbox mutants predicted to be defective in EAP interactions at this site ( Lemmon and Traub, 2012 ; Willox et al, 2014 ). In addition to the controversy as to the mechanism of action, pitstop is cytotoxic at concentrations not much higher than those required to inhibit CME ( Rosselli-Murai et al, 2018 ), perhaps as a result of its reported effects on spindle assembly ( Smith et al, 2013 ) and nucleocytoplasmic permeability ( Liashkovich et al, 2015 ). Thus, there remains a need for specific inhibitors of CME that work by rapid, well-defined mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phosphorylated Akt and PTEN preferentially localize to short-lived CCPs in MCF10A breast epithelial cells (Rosselli-Murai et al, 2018). Deletion of PTEN in these cells or addition of supplemental PIP 3 enhanced the initiation of short-lived CCPs.…”
Section: Localization Of Pi3k-akt Signaling Within Plasma Membrane Namentioning
confidence: 99%
“…In contrast, co-expression of ErbB2 leads to EGFR-dependent Akt activation that is clathrin-independent (Garay et al, 2015). Furthermore, PI3K/Akt signaling at clathrin nanodomains is directly influenced by the phosphatase activity of PTEN, through the control of PIP 3 abundance on the plasma membrane (Rosselli-Murai et al, 2018). Collectively, these studies support the notion that a subset of clathrin structures function as signaling nanodomains at the cell surface, as has been proposed for certain aspects of GPCR signaling (Eichel et al, 2016, 2018; Eichel and von Zastrow, 2018).…”
Section: Localization Of Pi3k-akt Signaling Within Plasma Membrane Namentioning
confidence: 99%